An experimental and theoretical stress-strain-damage correlation procedure for constitutive modelling of granite. (April 2019) - Bruning, Thomas; Karakus, Murat; Nguyen, Giang D.; Goodchild, David
Abstract: In this study, new theoretical and experimental stress-strain-damage correlation procedures for hard rock constitutive models are proposed. The damage-plasticity modelling framework is first supplied with the unified yield-failure criterion to describe the failure behaviour of granite under triaxial compression. This unified criterion allows the initial yield surface to evolve to a final failure surface through the utilisation of an appropriate damage evolution law. This evolution automatically captures the quasi-brittle behaviour of rocks under shearing at low confining pressure and ductile response under high confining pressure, as well as the transition from quasi-brittle to ductile reactions. In this theoretical sense, damage and plasticity are tightly coupled to govern the behaviour of rocks under different confining pressures without requiring any separate formulations for softening or hardening. Next, an innovative experimental correlation procedure is proposed to better link the experimental damage measure to stress states throughout triaxial loading. By obtaining full stress, strain and acoustic emission damage results from testing it was possible to construct a series of evolving yield surfaces from experiment. These surfaces, coupled with experimental damage evolution with respect to accumulated plastic strain, provide a comprehensive data set to a constitutive model for calibration. The results of numerical simulation show that this new method to incorporate coupled stress-strain-damage evolution characteristics directly from experiment removes the need for trial and error curve fitting. Also, by maintaining a closer link to detailed experimental results, the model is easier to calibrate and can be relied upon to predict the damage and stress states for compressive stress regimes. Finally, it is shown that the theoretical and experimental procedures can capture the key behaviours of granite under a range of confining pressures.